Experience with Nursing Students using Interactive Video Conferencing (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2016)
Interactive video conferencing is a means of communication that has revolutionised opportunities for reaching students over a vast distance as opposed to past practices when students or lecturers had to travel long distances for contact sessions. It is imperative in current challenging educational systems that each lecturer be acquainted with the modern technology in transmitting of knowledge and skills. The purpose of this article is to share my personal experience with Interactive videoconferencing with Nursing students. This method was challenging to me in the beginning, but as lecturers progressed it went well and students enjoyed the lectures according the statements made by themselves. This method, despite many challenges this teaching method has far reaching and long lasting effects with good and effective planning that will result in success.